2017
DOI: 10.1002/prot.25322
|View full text |Cite
|
Sign up to set email alerts
|

Predicting binding modes of reversible peptide-based inhibitors of falcipain-2 consistent with structure-activity relationships

Abstract: Falcipain-2 (FP-2) is a major hemoglobinase of Plasmodium falciparum, considered an important drug target for the development of antimalarials. A previous study reported a novel series of 20 reversible peptide-based inhibitors of FP-2. However, the lack of tridimensional structures of the complexes hinders further optimization strategies to enhance the inhibitory activity of the compounds. Here we report the prediction of the binding modes of the aforementioned inhibitors to FP-2. A computational approach comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 84 publications
0
25
0
Order By: Relevance
“…Replicate MD simulations were also performed when indicated by assigning random initial velocities drawn from a Maxwell-Boltzmann distribution to the atoms during the heating steps. More details concerning the EM protocols, treatment of nonbonded interactions, temperature and pressure control, timestep, etc., can be found elsewhere [44].…”
Section: Molecular Dynamics Simulations Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Replicate MD simulations were also performed when indicated by assigning random initial velocities drawn from a Maxwell-Boltzmann distribution to the atoms during the heating steps. More details concerning the EM protocols, treatment of nonbonded interactions, temperature and pressure control, timestep, etc., can be found elsewhere [44].…”
Section: Molecular Dynamics Simulations Setupmentioning
confidence: 99%
“…ΔG eff values were calculated using the GB-neck2 (GBn2) model available in the MMPBSA.py program [36]. This model was selected as it yielded good correlations with experimental results in a previous work that studied the interaction of FP-2 with peptide-based inhibitor [44]. The method was applied to either trajectories or energy-minimized single structures during rescoring steps, as mentioned earlier.…”
Section: Mm-gbsa Free Energy Calculationsmentioning
confidence: 99%
“…The year 2017 introduced the first computational study to predict the binding modes of FP-2 inhibitors according to the obtained SAR data of previous studies conducted for peptide inhibitors. The investigators proposed a new strategy to identify the molecular demands of a compound to efficiently bind to FP-2 in one complex [120] . One year later, the same group of investigators identified a promising novel anti-malarial drug (HTS07940).…”
Section: Screening Technology A) Sole Inhibitors For Fpsmentioning
confidence: 99%
“…The literature comprises a large number of inhibitors against FPs derived from both experimental and computational approaches. The identified inhibitors, which are either synthetic or from natural sources, fall into three main categories: peptide-based [31, 5456], non-peptidic [50, 5761]; and peptidomimetic [58, 62, 63]. Majority of the peptidic and peptidomimetic inhibitors have shown activity against FPs at nanomolar concentrations.…”
Section: Introductionmentioning
confidence: 99%